French Historiography of Central Asia. / Historiografía francesa de Asia Central - Tayshanova, Saltanat T.; Aitbayeva, Rauilya T.; Abzhapparova, Bibikhadisha Zh.; Aliyeva, Saule K.; Alpeissov, Amirzhan K. (Utopía y Praxis Latinoamericana, 1970)
ABSTRACT Article presents the analysis of historiography of French scientists concerning Central Asia in common and each of its republics separately. We have studied the works of leading French researches from 1991 to the present. The study has revealed, that region of Central Asia has lost its homogeneity: each state in the region is developing in its own way, according to its own model and has only its own international guidelines. A careful analysis leads to the need for a more accurate study of the system of analytical structures and their functioning within the framework of geostrategic and foreign policy discourse.RESUMENEl artículo presenta el análisis de la historiografía de los científicos franceses sobre Asia Central en común y cada una de sus repúblicas por separado. Se han estudiado las obras de las principales investigaciones francesas desde 1991 hasta el presente. El estudio ha revelado que la región de Asia Central ha perdido su homogeneidad: cada estado de la región se está desarrollando a su manera, según su propio modelo y tiene sus propias directrices internacionales. Un análisis cuidadoso conduce a la necesidad de un estudio más preciso del sistema de estructuras analíticas y su funcionamiento en el marco del discurso geoestratégico y de política exterior.